Clinical Study of Hearing Outcome After Type-I Tympanoplasty Using Temporalis Fascia as Graft - Kandel, Damodar; Pokharel, Apar; Bhandari, Ramesh; Aryal, Bivek; Bhandari, Chhanya; Sharma, Bibek (Journal of College of Medical Sciences-Nepal, 2021)
Background Chronic suppurative otitis media is a longstanding infection of the middle ear cleft characterized by persistent or recurrent aural discharge, deafness and perforation of tympanic membrane. Type I tympanoplasty is a surgical procedure that corrects tympanic membrane perforation. Methods Prospective study conducted on sixty-two patients of Chronic otitis media, mucosal type who underwent type I tympanoplasty in College of Medical Sciences, Bharatpur, Chitwan during a period of one year. Pure tone audiometry of the patients was done before the surgery and one month and three months following surgery and the hearing improvement was assessed in each case. P values were calculated by applying t test. Results In this study, graft uptake was highest (95%) in posterior perforations, 75% in anterior perforations and lowest (63.64%) in combined perforations. The mean hearing improvement one month following surgery was 7.16 dB and three months following surgery, it was 7.78 dB. Conclusions Chronic otitis media is a treatable cause of hearing loss. Type I tympanoplasty is a safe and effective method to remove the disease of the middle ear and reconstruct the tympanic membrane perforation.